Familial and individual predictors of obesity and insulin resistance in urban Hispanic children - Santiago-Torres, Margarita (Pediatr Obes, 2015)
BACKGROUND: High intake of sugar-sweetened beverages (SSB) has been suggested to contribute to the pediatric obesity epidemic, however, how the home food environment influence children’s intake of SSB among Hispanic families is still poorly understood. OBJECTIVES: To evaluate the relationships between the home food environment and Hispanic children’s diet in relation to weight status and insulin resistance (IR). METHODS: A food frequency questionnaire was administered to 187 Hispanic children (ages 10 to 14 years), and anthropometrics were measured. IR was estimated from fasting insulin and glucose levels using the homeostasis model assessment of insulin resistance (HOMA(IR)). Parents reported on family demographics and the home food environment. A structural equation modeling approach was applied to examine the hypothesized relationships among variables. RESULTS: The prevalence of childhood overweight and obesity was 52.8% and it was positively associated with HOMA(IR) (β=0.687, P <.0001). Children’s SSB consumption was positively associated with children’s BMI z-score (β=0.151, P <0.05) and subsequently to HOMA(IR). Children’s SSB consumption was predicted by home availability (β=0.191) and parental intake of SSB (β=0.419) (P <0.05). The model fit indices [X(2) = 45.821 (d.f. = 30, P > 0.01 and < 0.05), X(2)/d.f. = 1.53, RMSEA = 0.053 (90% C.I. = 0.016, 0.082), CFI = 0.904] suggested a satisfactory goodness-of-fit. CONCLUSIONS: The home food environment and parental diet seem to play an important role in the children’s access to and intake of SSB, which in turn predicted children’s weight status.